2015
DOI: 10.1016/j.jmii.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscess among children in a medical center in Central Taiwan

Abstract: Pyogenic liver abscess should be considered in children presenting with fever, abdominal pain, and leukocytosis with a high CRP level. Most cases involve a single lesion on right lobe of the liver. K. pneumoniae and Streptococcus spp. are the two most common pathogens. Drainage with adequate antibiotics has significantly good response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
5
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 6 publications
7
36
5
7
Order By: Relevance
“…2 The clinical features of pain and fever has also been noticed by others. 2 Male to female ratio was 1.4. Other studies have also found nearly same ratio.…”
Section: Discussionmentioning
confidence: 53%
“…2 The clinical features of pain and fever has also been noticed by others. 2 Male to female ratio was 1.4. Other studies have also found nearly same ratio.…”
Section: Discussionmentioning
confidence: 53%
“…Actually ultrasound was more widely used in clinical work due to universality of technology, ease of operation and higher cost performance, even as a tool to perform ultrasoundguild aspiration. It has been reported contrast-enhanced CT scan was done in PLA patients [16][17][18] , but owing to the potential risk of liver or renal function impaired and the consideration of economic burden, ultrasound became one of the main imaging examination method to diagnose PLA.…”
Section: Discussionmentioning
confidence: 99%
“…Culture-based techniques are the golden standard, and varies studies advanced more pathogens can be isolated through pus culture [18,20,21] . In our study the positive rate of blood or pus culture was not very high, it could be attribute to sample collection after prior antibiotic treatment of prehospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al 16) reported that fever and abdominal pain were the major manifestations of PLA. Other manifestations, such as diarrhea, vomiting, and weight loss are nonspecific.…”
Section: Discussionmentioning
confidence: 99%